The Environmental Kuznets Curve and Sustainable Economic Growth in Colombia - Gómez-Segura, Camilo Fabiam; Cerquera-Losada, Oscar Hernán; Acero-Cebay, Edwin Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper seeks to empirically test the Environmental Kuznets Curve (EKC) hypothesis in the emissions of carbon dioxide (CO₂) and nitrous oxide (N₂O) during the period 1990-2012 for 217 economies, using the World Bank database. A panel data model was carried out under three alternatives (fixed effects, random effects and first differences). The results obtained show that there is an inverted U relationship between environmental pollution (CO₂ and N₂O) and Gross Domestic Product (GDP) per capita as a measure of economic growth, with the fixed effects method generating consistent estimates when applying the Hausman test. However, the relationship between pollution and economic growth presents too low decreasing returns, which generates high turning points, mainly in emissions from CO₂.